The purification and identification of human blood serum proteins with affinity to the antitumor active RL2 lactaptin using magnetic microparticles - Manko, Nazar; Starykovych, Marina; Bobak, Yaroslav; Stoika, Rostyslav; Richter, Vladimir; Koval, Olga; Lavrik, Inna; Horák, Daniel; Souchelnytskyi, Serhiy; Kit, Yuriy (Biomedical chromatography, 2019)
The cytopoxic effect of RL2 lactaptin (the recombinant analog of proteolytic fragment of human kappa-casein) toward tumor cells in vitro and in vivo presents it as a novel promising antitumor drug. The binding of any drug with serum proteins can affect their activity, distribution, rate of excretion and toxicity in the human body. Here, we studied the ability of RL2 to bind to various blood serum proteins. Using magnetic microparticles bearing by RL2 as an affinity matrix, in combination with mass spectrometry and western blot analysis, we found a number of blood serum proteins possessing affinity for RL2. Among them IgA, IgM and IgG subclasses of immunoglobulins, apolipoprotein A1 and various cortactin isoforms were identified. This data suggests that in the bloodstream RL2 lactaptin takes part in complicate protein-protein interactions, which can affect its activity.
Keywords: kyseliny polymethakrylové; identification; RL2 antitumor agent; magnety; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Magnets; Caseins; lidé; rekombinantní proteiny; Recombinant Proteins; Antineoplastic Agents; protinádorové látky; kaseiny; Polymethacrylic Acids; Blood Proteins; krevní proteiny; magnetic microparticles; mass spectrometry and western blotting; purification; Chromatography, Affinity; spektrometrie hmotnostní - ionizace laserem za účasti matrice; human blood serum proteins; Microspheres; mikrosféry; chromatografie afinitní; Humans